Co-Investment Network of ERC-20 Tokens: Network Structure Versus Market Performance - Liu, Si-Hao; Liu, Xiao Fan (Frontiers in Physics, 2021)
Cryptocurrencies have attracted extensive attention from individual and institutional investors in recent years. In this emerging and inefficient capital market, the roles that institutional investors play can have a remarkable impact on the market. This paper investigates the ERC-20 token investment market from a network perspective. Using a dataset containing 317 ERC-20 tokens and their institutional investors at the end of June 2020, we construct a co-investment network of tokens connected by the sharing of institutional investors. Specifically, we examine whether the tokens' market embeddedness, measured by their network structural properties, can influence their market performance, as well as whether the tokens' structural similarity in the co-investment network can influence similarity of their market performance. Our results indicate that closeness centrality, strength centrality, and clustering coefficient have a significant impact on trading volume and liquidity of the market. And there is a significantly positive correlation between the Jaccard similarity index and tokens' market performance similarity. This work demonstrates the non-negligible influence of the institutional investors and the diffusion of such influence through co-investment relationships in the cryptocurrency market. We expect the analysis could further enhance the understanding of the inefficiency and vulnerability of this emerging market.